2009
DOI: 10.1016/j.neuron.2008.10.054
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Functional Maturation of Nascent Dendritic Spines

Abstract: SUMMARY Spine growth and retraction with synapse formation and elimination plays an important role in shaping brain circuits during development and in the adult brain. Yet the temporal relationship between spine morphogenesis and the formation of functional synapses remains poorly defined. We imaged hippocampal pyramidal neurons to identify spines of different ages. We then used two-photon glutamate uncaging, whole-cell recording, and Ca2+ imaging to analyze the properties of nascent spines and their older nei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
206
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 246 publications
(220 citation statements)
references
References 72 publications
14
206
0
Order By: Relevance
“…(i) The two types of structures and the two types of receptors at the PSD-NMDARs are generally located in the central region of the PSD, whereas AMPARs occupy the peripheral regions of the PSD (8,10). (ii) The number of AMPAR-type structures is positively correlated with PSD size, and the number of NMDARtype structures is independent of PSD size, in agreement with the results from other methods such as serial-section immuno-EM (8,10) and two-photon uncaging of glutamate on dendritic spines (69)(70)(71). (iii) The 176-nm diameter of the central NMDAR cluster at PSDs from this work matches the minimum PSD diameter of ∼180 nm for PSDs lacking AMPARs (8).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…(i) The two types of structures and the two types of receptors at the PSD-NMDARs are generally located in the central region of the PSD, whereas AMPARs occupy the peripheral regions of the PSD (8,10). (ii) The number of AMPAR-type structures is positively correlated with PSD size, and the number of NMDARtype structures is independent of PSD size, in agreement with the results from other methods such as serial-section immuno-EM (8,10) and two-photon uncaging of glutamate on dendritic spines (69)(70)(71). (iii) The 176-nm diameter of the central NMDAR cluster at PSDs from this work matches the minimum PSD diameter of ∼180 nm for PSDs lacking AMPARs (8).…”
Section: Discussionsupporting
confidence: 83%
“…These distinguishing properties of AMPAR-and NMDAR-type structures matched the properties of AMPARs and NMDARs at the PSD shown by immuno-EM (8,10). Two-photon uncaging of glutamate on dendritic spines illustrated a similar dependence of AMPAR and NMDAR responses on spine size (69,70). Thus, AMPAR-type and NMDAR-type structures, as classified by EM tomography, are coextensive with AMPARs and NMDARs, respectively.…”
Section: Analysis Of Ampar-and Nmdar-type Structures By Em Tomographymentioning
confidence: 54%
“…Uncaging of MNI-glutamate was achieved as previously described (49). In brief, the LFU stimulus consisted of 90 pulses (720 nm; 6-8 mW at the sample) of 1-ms duration delivered at 0.1 Hz by parking the beam at a point ∼0.5 μm from the center of the spine head.…”
Section: Methodsmentioning
confidence: 99%
“…Such delays may differ among learning protocols and systems involved. Thus, some studies have suggested that synapses involving new spines or filopodia are assembled within the first 1-3 hours after potentiation 101 , whereas other studies have provided evidence for delays of 12-18 hours 102 . The longer delays provide a potential mechanism to relate learning to the consolidation of memories, for example, during sleep.…”
Section: Is It Inhibition or Excitation?mentioning
confidence: 99%